1997
DOI: 10.1002/(sici)1096-911x(199703)28:3<213::aid-mpo12>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Successful management with interferon alpha‐2a after prednisone therapy failure in an infant with a giant cavernous hemangioma

Abstract: A giant cavernous hemangioma of the left arm subcutaneous infusions of interferon alphawith severe thrombocytopenia and consumptive 2a.Coagulopathy rapidly improved and transfucoagulopathy was observed in a neonate. Initial sions were drastically reduced. The hemangioma treatment with prednisone, platelet transfusions, regressed progressively and disappeared after 4 and clotting replacement failed to control the months of treatment. Med. Pediatr. Oncol. 28: bleedings. The child was then treated with daily 213-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Interferon-α-2a and interferon-α-2b have gained recent attention for the treatment of hemangiomas. [93][94][95][96][97][98][99][100][101][102][103][104][105] Interferon-α-2a was initially conceived as an antiviral agent. During the course of clinical trials in patients with AIDS, regression of Kaposi sarcoma lesions was observed in treated patients.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferon-α-2a and interferon-α-2b have gained recent attention for the treatment of hemangiomas. [93][94][95][96][97][98][99][100][101][102][103][104][105] Interferon-α-2a was initially conceived as an antiviral agent. During the course of clinical trials in patients with AIDS, regression of Kaposi sarcoma lesions was observed in treated patients.…”
Section: Managementmentioning
confidence: 99%
“…95 Treatment of hemangiomas with interferon-α-2a or α-2b has generally been reserved for those lesions that are believed to be life-threatening or possibly causing function-impairing sequelae or severe cervicofacial disfigurement. [93][94][95][96][97][98][99][100][101][102][103][104][105] It has been particularly used for those lesions that appear to be resistant to corticosteroids. The usual starting dosage is 1 million units given subcutaneously nightly.…”
Section: Managementmentioning
confidence: 99%
“…Disseminated intravascular coagulation can often be controlled with heparin or low-molecular-weight heparin, usually delivered subcutaneously, or antithrombin, c~r~c~ntr~te; however, occasionally local radiation therapy or injections of sclcrosing agents have been reported to be beneficial (4,97,99). Of particular interest are recent reports of the efficacy of alpha interferon in treating the Kasabach-Merritt syndrome (100,101). Also, patients may develop localized but extensive deep vein thrombosis in association with giant cavernous hemangiomata (102).…”
Section: Pseudoxanthoma Elasticummentioning
confidence: 99%
“…Interferon-a (IFN-a) has shown promise in the treatment of vascular lesions (21)(22)(23)(24). This agent is reported to inhibit endothelial cell proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%